FINANCIAL DISTRESS ANALYSIS IN BANKING: WICH METHODS IS THE MOST ACCURATE? - Nawirah, Nawirah; Permatasari, Ditya; Wahidah, Maulidina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This study aims to analyze financial distress from several methods, Altman, Zmijewski, Grover, Springate, Ohlson, and CA-Score. The object of this research is banks that have been listed on the Indonesia Stock Exchange. The period in this research is from 2016 to 2020. This type of research is quantitative research with a descriptive approach. This research uses secondary data from banks’ financial statements. The sampling technique used the purposive sampling method and uses the calculation of the financial ratios of each method, while hypothesis testing uses the accuracy level and error type with Microsoft Excel. This study shows that the Altman method has an accuracy rate of 9.09%, the Zmijewski method has an accuracy rate of 9.09%, the Grover method has an accuracy rate of 90.91%, the Springate method has an accuracy  rate of 0%, the Ohlson method and CA-Score has the same accuracy level of 100%. The Ohlson and CA-Score method shows the most accurate method in predicting bankruptcy in banking companies. This research implies that the various existing method is expected to determine the most accurate method that can be applied in predicting financial distress in banking.